Implikasi RPJMN 2010-2014 Sektor Pendidikan terhadap Manajemen Pengembangan Kurikulum Pendidikan Dasar dan Menengah - Herry Widyastono (Jurnal Pendidikan dan Kebudayaan, 2012)
The goal of writing this article is to set a management strategy of national curriculum development, regional curriculum, and school curriculum in accordance with RPJMN 2010-2014 education sector. The results of the study are as follows: a) In general, distinguished between centralized curriculum development management (centralized), spread (decentralized), and central-decentralized; b) KTSP is the operational curriculum developed by and implemented in each school, with reference to the National Education Standards. So the KTSP is the central -decentralized management of curriculum development, c) In general, teachers are adapting even adopt KTSP from other schools that do not necessarily correspond to the characteristics of their schools, d) The authorization better tiered, ranging from the authority of the central government, provincial, district/city governments, and schools. Based on these conclusions, it is recommended that the relevant work units, in accordance with the duties and functions, shall: a) preparing and determining the Regulation of Minister of Education and Culture on the National Curriculum Arrangement, District, and School, as well as all the conflicting rules regarding curriculum revoked and is no longer valid; b) socialization to all education stakeholders at national and regional levels, c) giving technical and professional training on curriculum development, d) giving training for educators and education personnel, and (e) prepare and copying all the necessary learning tool. ABSTRAK Tujuan penulisan untuk menyusun rencana strategi pengembangan kurikulum nasional, daerah, dan satuan pendidikan sesuai amanah RPJMN 2010-2014 sektor pendidikan. Hasil kajian menyimpulkan: a) Secara umum dibedakan antara manajemen pengembangan kurikulum terpusat (sentralistik), tersebar (desentralistik), dan sentral-desentral; b) KTSP adalah kurikulum operasional yang disusun oleh dan dilaksanakan di masing-masing satuan pendidikan, dengan mengacu Standar Nasional Pendidikan. KTSP merupakan manajemen pengembangan kurikulum sentral-desentral; c) Pada umumnya guru hanya mengadaptasi bahkan mengadopsi KTSP dari satuan pendidikan lain yang belum tentu sesuai dengan karakteristik satuan pendidikannya; d) Pemberian kewenangan lebih baik berjenjang, mulai dari kewenangan pemerintah pusat, pemerintah provinsi, pemerintah kabupaten/kota, dan satuan pendidikan. Berdasarkan kesimpulan tersebut, direkomendasikan agar unit-unit kerja terkait, melakukan: a) penyusunan dan penetapan Peraturan Menteri Pendidikan dan Kebudayaan tentang Penataan Kurikulum Nasional, Daerah, dan Sekolah; b) sosialisasi kepada seluruh pemangku kepentingan pendidikan di tingkat pusat dan daerah; c) bantuan profesional pengembangan kurikulum dan pembinaan teknis kepada para penyelenggara pendidikan; d) pelatihan bagi para pendidik dan tenaga kependidikan; dan e) penyiapan dan penggandaan seluruh sarana pembelajaran yang diperlukan.